The Vertebral Bone Marrow clot as cell therapy and multifunctional bioscaffold for spinal fusion surgery: protocol for a randomized clinical trial - Maria Sartori; Giuseppe Tedesco; Paolo Spinnato; Antonio Mazzotti; Antonio Mazzotti; Alessandro Gasbarrini; Alessandro Gasbarrini; Cesare Faldini; Cesare Faldini; Marco Miceli; Gianluca Giavaresi; Francesca Salamanna (Frontiers in Medicine)
IntroductionSpinal fusion (SF) represents a commonly performed orthopedic surgical procedure, and to enhance its success rate, various adjunctive therapies have been explored, including the application of local autografts, bone allografts, and different formulations of Bone Marrow Aspirate (BMA). Among these, Vertebral Bone Marrow Aspirate (vBMA) clot emerges as an innovative and promising avenue for future development. The primary challenge in using vBMA clot for SF procedures lies in the lack of high-level clinical evidence demonstrating whether its combination with bone allograft chips is superior to using bone allograft chips alone. Additionally, there is a shortage of preclinical studies investigating the intrinsic biological, anti-inflammatory, and antibacterial properties of vBMA clots.Methods and analysisPatients with degenerative lumbar spine diseases (aged 18–80 years, with ≤5 levels involved) are randomly assigned in a 1:1 ratio to undergo SF with autologous vBMA clot associated with bone allograft chips or bone allograft chips alone by a blinded experimenter, who is not involved in the RCT. The primary aim is to evaluate the SF rate and time in the two groups as well as consider age and gender differences. SF rate and time are evaluated with CT scans and x-rays and performed preoperatively and at 1, 3, 6, and 12 months of follow-up (FU). Using the Brantigan classification, quantitative CT analyses of facet joint space density are calculated at baseline and in follow-up controls to complement the standard qualitative visual scale. CT and X-rays will be assessed in a blinded manner by a diagnostic and interventional radiologist. The secondary outcome is to evaluate the pseudoarthrosis rate estimated using the Brantigan classification, and the clinical outcomes are assessed using the Visual Analog Scale (VAS), the Oswestry Disability Index (ODI), and the Short Form 36 Health Survey (SF-36) questionnaire by comparing baseline (pre-surgery) values with those at 1, 3, 6, and 12 months of FUs. All scores and the questionnaire will be evaluated by a blinded assessor. Complications are also recorded and classified as early (major and minor) or late, according to the time of occurrence and findings at 12 months post-surgery. Finally, the preclinical project outcome is to define the biological and anti-inflammatory properties of vBMA clot and demonstrate its antibacterial effect, assessing age and gender differences and including an examination of their interactions.Clinical trial registrationClinicalTrials.gov, identifier NCT05947175.